Transitions between flat epithelial atypia and low-grade ductal carcinoma in situ of the breast - Aulmann, Sebastian; Braun, Lisa; Longerich, Thomas; Penzel, Roland; Schirmacher, Peter; Sinn, Peter (The American journal of surgical pathology, 2012)
Flat epithelial atypia (FEA) of the breast typically is a localized alteration involving only few, neighboring terminal ducto-lobular units. However, occasionally there are cases with extensive FEA and morphologic evidence of direct transitions between FEA and classical low-grade ductal carcinoma in situ (lg-DCIS). To investigate the relationship between FEA and DCIS in these cases, we microdissected multiple foci of the respective lesions in a series of 10 cases and performed comparative allelotyping using a panel of 14 loss of heterozygosity markers. In addition, phylogenetic tree models were calculated on the basis of mitochondrial DNA sequencing to visualize the clonal relationship of the different lesions. FEA and lg-DCIS shared the majority of chromosomal imbalances; loss of diverging alleles was not detected in any of the 10 cases. Mitochondrial DNA sequencing and phylogenetic tree clustering revealed direct transitions between FEA and lg-DCIS in all 10 cases. However, in 3 patients, additional foci of FEA were present, which were not directly related to the rest of the FEA and the lg-DCIS. Our data demonstrate the presence of direct transitions between FEA and lg-DCIS and support the interpretation of FEA as part of the low-grade pathway in the development of breast cancer.